The relationship between incidence of delay in offering care to the patient and nurses professional commitment - Mahboobeh shali; soodabeh Joolaee; Abbas Hooshmand; Mansoureh Sepehrinia; hamid haghani (Zanjan University of Medical Sciences and Health Services, 2016)
Background and Objectives: Delay in patient care is the most common error that threatens patient safety and increases mortality, and hospital costs. This study investigated the relationship between delay in patient care and nurses professional commitment. Materials and Methods: This is a descriptive correlational study. Through a stratified sampling method, 300 nurses were selected from Tehran University of Medical Sciences teaching hospitals. Data were collected by a three-part questionnaire consisting of demographic data, the nursechr('39')s professional commitment scale, and delay in care questionnaire. Data were analyzed by SPSS software version 16 using descriptive statistics and Pearsonchr('39')s correlation coefficient. Results: The participants were between 22-50 years old and the majority of them were women (86.7%) and married (64%). The mean score for delay in patient care was 21.54 for each nurse in the past 3 months (high) and it was 86 for professional commitment and there was a significant weak and reverse relationship between delay in patient care, and nurses professional commitment (p<0/008, R=-0/15). Conclusion: Patient care delay is a common error in health system regardless of individual factors such as professional commitment; other factors must also be identified and addressed. Strategies to report the errors and get help from other members of the care team contribute to reducing the complications of such errors.